IMPROVING HEALTH EDUCATION IN KENYA - Eisemon, Thomas Owen; Patel, Vimla (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1988)
Adopting new health practices is not simply a matter of being told what to do and doing what one is told. The primary health care interventions that are currently being introduced in Kenya and developing countries to reduce infant mortality require parents to perform complex cognitive tasks. These involve making inferences from knowledge of human biology and disease processes that may not be acquired from health instruction provided in schools or through public health campaigns. What is needed to design more effective health education programs is a better understanding of the knowledge structures and cognitive strategies that are involved in comprehending procedures associated with modern health care practices. RÉSUMÉ L’adoption de nouvelles pratiques sanitaires n’est pas seulement le fait d’ordres reçus que l’on applique avec ardeur. Les pratiques sanitaires introduites au Kenya et dans certains pays en voie de développement pour réduire le taux de mortalité infantile exigent des parents qu’ils accomplissent des tâches cognitives complexes. Cela implique des déductions à partir des connaissances de la biologie humaine et des processus pathologiques qu’on n’acquiert pas dans le cadre de l’instruction donnée à l’école ou des campagnes de santé publique. Ce qu’il faut pour concevoir des programmes d’éducation sanitaire plus efficaces, c’est de mieux comprendre les structures et les stratégies cognitives qui contribuent à la compréhension des procédures liées aux pratiques sanitaires modernes.